Fiber pathways connecting cortical areas relevant for spatial orienting and exploration. Issue 3 (2nd January 2013) - Suchan, Julia; Umarova, Roza; Schnell, Susanne; Himmelbach, Marc; Weiller, Cornelius; Karnath, Hans‐Otto; Saur, Dorothee
Abstract : By implementing a task that closely resembled a clinical test for diagnosing spatial neglect in stroke patients, Himmelbach et al. (2006 : Neuroimage 32:1747–1759) found significantly increased activation during active exploration in those cortical areas in healthy subjects that are known to induce spatial neglect in case of a lesion. The present study investigated whether direct intra‐hemispheric cortico‐cortical connections could be found between these activated clusters using a probabilistic fiber‐tracking approach in 52 healthy subjects. We found that parts of the extreme capsule (EmC) and the middle longitudinal fascicle (MdLF) connected the functional cluster in the prefrontal cortex with the superior temporal cortex and the temporo‐parietal junction (TPJ) area in both hemispheres. The activation peak in the TPJ was additionally connected to the inferior frontal cortex by parts of the arcuate fascicle and the superior longitudinal fascicle (SLF II) in the right hemisphere. Our study elucidates the connections constituting the perisylvian network for spatial orienting and attention. Hence, we complement the knowledge from patients suffering from spatial neglect by giving first empirical evidence for the complete postulated network in healthy subjects. Hum Brain Mapp 35:1031–1043, 2014. © 2013 Wiley Periodicals, Inc.